2015
DOI: 10.1055/s-0034-1393730
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Interpersonal Injury in a Pediatric Oral and Maxillofacial Trauma Population: A Retrospective Review of 1,192 Trauma Patients

Abstract: The social, financial, and health implications of adult alcohol-related oral and maxillofacial trauma have been recognized for several years. Affordability and widespread accessibility of alcohol and issues of misuse in the pediatric trauma population have fostered concerns alcohol may be similarly implicated in young patients with orofacial trauma. The aim of this study was to review data of pediatric facial injuries at a regional maxillofacial unit, assess the prevalence of alcohol use, and review data of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…48 It has been suggested that more severe cases of maxillofacial injury may be correlated with longer hospital stays and higher hospitalization costs due to the considerable economic expense incurred in the emergency department as well as peri- and intraoperatively. 12,24,49 Nonetheless, no studies to date have been able to confirm these hypotheses. The authors believe the reason that BAC failed to impact hospitalization outcomes is the insufficient sample of patients with documented BAC levels (n = 285).…”
Section: Discussionmentioning
confidence: 99%
“…48 It has been suggested that more severe cases of maxillofacial injury may be correlated with longer hospital stays and higher hospitalization costs due to the considerable economic expense incurred in the emergency department as well as peri- and intraoperatively. 12,24,49 Nonetheless, no studies to date have been able to confirm these hypotheses. The authors believe the reason that BAC failed to impact hospitalization outcomes is the insufficient sample of patients with documented BAC levels (n = 285).…”
Section: Discussionmentioning
confidence: 99%